Cellular redox regulation, signaling, and stress response in plants. Issue 9 (2nd September 2014) - Shigeoka, Shigeru; Maruta, Takanori
Abstract: Cellular and organellar redox states, which are characterized by the balance between oxidant and antioxidant pool sizes, play signaling roles in the regulation of gene expression and protein function in a wide variety of plant physiological processes including stress acclimation. Reactive oxygen species (ROS) and ascorbic acid (AsA) are the most abundant oxidants and antioxidants, respectively, in plant cells; therefore, the metabolism of these redox compounds must be strictly and spatiotemporally controlled. In this review, we provided an overview of our previous studies as well as recent advances in (1) the molecular mechanisms and regulation of AsA biosynthesis, (2) the molecular and genetic properties of ascorbate peroxidases, and (3) stress acclimation via ROS-derived oxidative/redox signaling pathways, and discussed future perspectives in this field. Graphical abstract: : Cellular redox states, which are characterized by the balance between oxidant and antioxidant pool sizes, are involved in plant stress acclimation.